A retrospective analysis of parasitic diseases diagnosed by tissue biopsy: a 7- year study - Manandhar , U; Karki , S; Shrivastav , S (Journal of Institute of Medicine Nepal, 2018)
Introduction: There are wide varieties of parasites that can infect humans involving various tissues and organs. Parasitic diseases are common in developing countries associated with poverty and poor sanitation. Non-endemic developed areas also show increasing trend of disease as a result of immigration. Morphological identification of parasitic structure along with inflammatory reaction in the surrounding tissue forms the mainstay of diagnosis of parasitic diseases on histopathology. Methods: The present study was a retrospective study carried out over a period of 7 years from 2010– 2016 in the department of Pathology of TUTH, Kathmandu. Results: 121cases (0.25%) of tissue parasites out of the total 47,220 biopsy specimen submitted for histopathological examination during the seven year period was observed. There was increasing rate of parasitic infection from 0.19 to 0.34% during 7- year period. Eight different types of parasites were detected. Hydatid cyst was the commonest (57 %) followed by Cysticercosis (35 %), Giardiasis (2%), Amoebiasis (2%) and one each of Myiasis, Fascioliasis, Tungiasis and Trichuriasis. The host tissue response to the cysticercosis and hydatid cyst showed fibrosis with inflammatory cell infiltrations composed of eosinophils, palisaded histiocytes, multinucleated giant cells. None of the cases showed well formed granulomas. All three cases of Giardiasis showed normal villi to crypt ratio with only increase in intraepithelial lymphocytes. Colonic mucosa in tichuriasis and amoebiasis showed increased eosinophils in lamina propia. Adjacent tissue in myiasis showed necrosis. Liver tissue in fascioliasis showed multiple well-formed granulomas and dense sheets of eosinophils and mononuclear cells. Conclusion: Parasitic infections are common around the world. Histopathological analysis plays an important role in diagnosis of tissue parasitic disease. Histopathological features in response to parasitic invasion are important for differential diagnosis and often confirms the presence of parasitic infestation. The commonest parasitic infections were hydatid disease and cysticercosis. So these should be kept in the differential diagnosis of cystic lesion in both endemic and non-endemic areas. Improvement in sanitation and personal hygiene helpful in preventation of parasitic infestation.